Hamman's Syndrome: A Rare Cause of Chest Pain in a Postpartum Patient - Khurram, Daniyeh (Case Rep Pulmonol, 2015)
Hamman's syndrome is a rare condition represented by spontaneous pneumomediastinum and subcutaneous emphysema. Excessive Valsalva maneuver during vaginal delivery and excessive retching, coughing, and straining are frequently reported causes. The incidence of Hamman's syndrome is believed to be 1 in 100,000 deliveries. The pathophysiology of this condition is rupture of alveoli and seepage of air through bronchovascular connective tissue. Diffusion of air to subcutaneous tissues results in subcutaneous emphysema. In most cases, it is a benign condition and resolves spontaneously. In life-threatening cases, a cardiac tamponade can ensue. Chest X-ray is a useful early diagnostic technique. We report a case of a twenty-four-year-old female who was diagnosed with Hamman's syndrome after prolonged, exhaustive labor.